2015
DOI: 10.1149/06601.0015ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Failure Mechanisms in AlGaN/GaN HEMTs Irradiated with 2MeV Protons

Abstract: GaN high electron mobility transistors (HEMTs) have shown the potential to be extremely tolerant of the space radiation environment. AlGaN/GaN HEMT structures on three different substrates were exposed to proton irradiation at fluences up to 6x10 14 cm-2 , which resulted in a 30% reduction in mobility and saturation current density. Dynamic ON-resistance measurements demonstrated increased degradation by a factor of 10 under off-state quiescent voltage stress conditions. High resolution transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Especially, studies on the irradiation effects of protons occupying the majority of low earth orbits (LEO) were carried out [5,6,7]. In general, AlGaN/GaN HFETs irradiated with protons exhibit a positive shift in the threshold voltage ( V th ) and a reduction in the drain current ( I DS ), which can be attributed to the displacement damage near the two-dimensional electron gas (2-DEG) [8,9]. Exceptionally, the improvement of carrier concentration also has been reported at a relatively low dose [10].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, studies on the irradiation effects of protons occupying the majority of low earth orbits (LEO) were carried out [5,6,7]. In general, AlGaN/GaN HFETs irradiated with protons exhibit a positive shift in the threshold voltage ( V th ) and a reduction in the drain current ( I DS ), which can be attributed to the displacement damage near the two-dimensional electron gas (2-DEG) [8,9]. Exceptionally, the improvement of carrier concentration also has been reported at a relatively low dose [10].…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6] It has been shown that AlGaN/GaN HEMTs have minimal changes in resistance, mobility, and device performance with MeV scale proton fluences of 5E13 H + /cm 2 while larger fluences (1E14 H + /cm 2 ) can create charge traps, which reduce the electron mobility and increase the carrier concentration. [7][8][9] Several studies have shown that AlGaN/GaN HEMTs are highly sensitive to their substrates and passivation layers. In particular, it has been shown that switching to a AlN-passivated layer improves transistor performance, 10 while switching to a GaN substrate reduces threading dislocation densities by 4 orders of magnitude.…”
mentioning
confidence: 99%